Introduction to Child Development / Fifth Edition - Dworetzky John P (West Publishing Company, 1993)
Foundations of Development, An Introduction to Development: History and Research, Inheritance and the Biological Foundations of Development, Beginning of Life: Birth and Infancy, Conception and Prenatal Development and Birth, Growth and Maturation and Individual Differences, Neural and Sensory and Perceptual Development, Infant Social and Emotional Development, The Developing Child: Learning and Language and Cognition, Learning, Language Development, Cognitive Development I: Historical Foundations, Cognitive Development II: Modern Perspectives, Intelligence and Individual Differences, The Developing Child: Social Process, Socialization and Personality Development, The Development of Sexuality and Sex Roles, Peers and School and the Social Environment, The Development of Morality and Self-Control, Child Development in Other Cultures, Children with Special Needs, Adolescence, Adolescent Physical and Cognitive Development, Adolescent Social and Personality Development.